Openness to Experience Rather Than Overexcitabilities: Call It Like It Is. (July 2016) - Vuyk, M. Alexandra; Krieshok, Thomas S.; Kerr, Barbara A.
Openness to experience is a personality factor in the five-factor model of personality, and it is composed of six facets. Facets of openness appear conceptually analogous to overexcitabilities (OEs), which are displays of inner energy guiding individuals toward advanced potential according to the theory of positive disintegration. This study examined the similarity of OEs to corresponding openness to experience facets in a sample of 149 creative adolescents and adults and 312 adults from the general population (total N = 461). Exploratory structural equation modeling tested competing models in which each OE and corresponding openness facet were modeled as separate factors and as joint factors. The separate-factor model had acceptable fit but uninterpretable loadings, while the joint-factor model had acceptable fit and interpretable loadings; thus, openness seems to encompass OEs. Accordingly, the field should align with well-researched psychological theories like the five-factor model of personality and begin to talk about openness rather than OEs.